2020
DOI: 10.3390/ijms21041429
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic Factor 1 (NR5A1) Activates ATF3 Transcriptional Activity

Abstract: Steroidogenic Factor 1 (SF-1/NR5A1), an orphan nuclear receptor, is important for sexual differentiation and the development of multiple endocrine organs, as well as cell proliferation in cancer cells. Activating transcription factor 3 (ATF3) is a transcriptional repressor, and its expression is rapidly induced by DNA damage and oncogenic stimuli. Since both NR5A1 and ATF3 can regulate and cooperate with several transcription factors, we hypothesized that NR5A1 may interact with ATF3 and plays a functional rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A study of Hill et al demonstrated that DDC-induced chronic inflammation could prompt rapid progression of intrahepatic cholangiocarcinoma [43]. NR5A1 is an orphan nuclear receptor which is proved to be essential for sexual differentiation and development of multiple endocrine organs, as well as the proliferation of cancer cells [44]. Evidences have shown that PDCD4 plays a critical role in the progression of several tumors [45][46][47], and serves as a tumor suppressor in PCa to modulate tumor growth and castration resistance [48].…”
Section: Discussionmentioning
confidence: 99%
“…A study of Hill et al demonstrated that DDC-induced chronic inflammation could prompt rapid progression of intrahepatic cholangiocarcinoma [43]. NR5A1 is an orphan nuclear receptor which is proved to be essential for sexual differentiation and development of multiple endocrine organs, as well as the proliferation of cancer cells [44]. Evidences have shown that PDCD4 plays a critical role in the progression of several tumors [45][46][47], and serves as a tumor suppressor in PCa to modulate tumor growth and castration resistance [48].…”
Section: Discussionmentioning
confidence: 99%
“…The steroidogenic factor-1 (SF-1) gene is an orphan nuclear receptor encoded by the Ftz-Fl gene, which is one kind of the atypical nuclear receptor [4]. As the main regulator of cholesterol metabolism, SF-1 can activate the cholesterol migration and the expression of genes related to adrenal steroidogenesis and plays an important role in the biosynthesis and development of steroid hormones [5,6].…”
Section: Introductionmentioning
confidence: 99%